Impaired Emotion Recognition after Left Hemispheric Stroke: A Case Report and Brief Review of the Literature - Hugo P. Aben; Yael D. Reijmer; Johanna M. A. Visser-Meily; Jacoba M. Spikman; Geert Jan Biessels; Paul L. M. de Kort; PROCRAS Study Group (Case Reports in Neurological Medicine)
Impaired recognition of emotion after stroke can have important implications for social competency, social participation, and consequently quality of life. We describe a case of left hemispheric ischemic stroke with impaired recognition of specifically faces expressing fear. Three months later, the patient’s spouse reports that the patient was irritable and slow in communication, which may be caused by the impaired emotion recognition. The case is discussed in relation to the literature concerning emotion recognition and its neural correlates. Our case supports the notion that emotion recognition, including fear recognition, is regulated by a network of interconnected brain regions located in both hemispheres. We conclude that impaired emotion recognition is not uncommon after stroke and can be caused by dysfunction of this emotion-network.